Implementación de estrategias de la comunicación no violenta y la educación emocional en el aprendizaje de un segundo idioma - Madrigal Villegas, Vera (2014)
This paper aims to combine Nonviolent Communication (NVC) and Emotional Education to develop strategies that contribute to increase motivation in EFL students. These strategies facilitate students’ learning, leading them to adopt positive attitudes towards learning a second language without feeling fear, guilt, or shame. Since many students have been educated to judge what they do or think about themselves in terms of what is considered right and wrong in society, this behavior leads to self-correction. However, when learning a second language, adults can be frustrated when they make common mistakes in the target language. Therefore, this research aims to find a way for students to reinforce positive self-correction in order to facilitate communication and avoid frustration. Furthermore, this study presents two cases of students majoring in Bachillerato en la Enseñanza del ingles from Universidad Nacional of Costa Rica, as a study to determine how effective can be to apply techniques based on emotional education and NVC. Furthermore, this paper attempts to raise awareness of the importance of helping out adult learners to identify emotions and needs, while developing skills to overcome barriers for their successful learning.